Development E-Worksheet of Reaction Rate Based on RADEC Learning Model with the Help of Liveworksheet - Nofita, Agnes; Yerimadesi, Yerimadesi (MANAZHIM, 2024)
The goal of this study is to develop reaction rate E-Worksheet based on RADEC learning model with the help of liveworskheet and analyze the quality of E-Worksheet developed. This Research and Development (R&D) study was developed utilizing the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate.. The research was limited to the develop stage, namely validity test and practicality test. The instruments used were validity and practicality questionnaires. The validation process involved three lecturers from the UNP Chemistry Department and two chemistry teachers from Senior High School Negeri 1 Batang Kapas. The practicality test was conducted by two chemistry teachers and twenty-eight eleventh-grade students (Phase F) from the same school during the January to June 2024 semester. The validity test results were analyzed using Aiken's V, while the results of the practicality test with a percentage of the achievement score. From the results of the research analysis, the Aiken's V value was 0.87 with a valid category. The results of the practicality test from teachers and students respectively obtained a percentage value of 88% and 93%. The research findings indicate that the reaction rate E-Worksheet based on the RADEC learning model with the help of liveworksheet for Phase F of Senior High School is valid and practical, so it can be continued to the next research for effectiveness testing.